Mangiferin Mitigates Lipopolysaccharide-Induced Lung Injury by Inhibiting NLRP3 Inflammasome Activation - Li N (Dove Medical Press, 2021)
Ning Li,* Rui Xiong,* Ruyuan He, Bohao Liu, Bo Wang, Qing Geng Department of Thoracic Surgery, Renmin Hospital of Wuhan University, Wuhan, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Wang; Qing GengDepartment of Thoracic Surgery, Renmin Hospital of Wuhan University, Jiefang Road 238, Wuhan, 430060, People’s Republic of ChinaEmail rmh_wb@whu.edu.cn; gengqingwhu@whu.edu.cnScope: Mangiferin (MF) is a natural phytopolyphenol, which displays potential pharmacological properties involving antibacterial, anti-inflammation, antioxidant and anti-tumor. However, little is known about the roles of MF in lung injury. The aim of this study is to demonstrate the modulatory effects and molecular mechanisms by which MF operates in sepsis-induced lung injury.Methods and Results: To examine the protective properties of MF, an in vivo model of lipopolysaccharide (LPS)-induced lung injury in mice and an in vitro model of LPS-treated J774A.1 cells were established, respectively. The results revealed that MF treatment significantly relieved LPS-induced pathological injury and inflammatory response in murine lung tissues. Meanwhile, MF treatment also inhibited nucleotide-binding oligomerization domain (NOD)-like receptor family, pyrin domain-containing protein 3 (NLRP3) inflammasome activation and pyroptosis induced by LPS. In macrophage-specific NLRP3 deficiency mice treated with LPS, MF showed little protective effects. NLRP3 overexpression by adenovirus could also offset the beneficial effects of MF in LPS-treated J774A.1 cells. Furthermore, we found that MF could suppress the expression of NLPR3 and pyroptosis of macrophages by inhibiting the nuclear translocation of the nuclear factor-κB (NF-κB) subunits P50 and P65.Conclusion: MF protects against lung injury and inflammatory response by inhibiting NLRP3 inflammasome activation in a NF-κB-dependent manner in macrophages, which provides a promising therapeutic candidate for the treatment of lung injury.Keywords: mangiferin, lung injury, NLRP3, P65